BERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PERJANJIAN E-COMMERCE - Priyono, Ery Agus (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACT The presence of e-commerce in the world of conventional agreements marks a dramatic technological change in all aspects of life, especially in the world of trade. The link created in conventional trading procedures, which at first cannot be eliminated becomes meaningless. Trade becomes easier, cheaper, and faster and ultimately encourages the growth of the creative economy in various fields in various classes. E-commerce as a yield of advances in information technology (the internet) has revealed a veil that has hindered the growth of the community's economy because it has been hit by bureaucracy, capital, fixed assets such as businesses. Technological advances in the field of information that have a large contribution to the economic growth of a society must be grateful, but in other situation an adequate legal umbrella is needed as a safeguard that provides a conducive business climate. This paper aims to reveal the availability of legal rules that can provide security for business people and the consumer community both in terms of public law and private law. The study method used is a normative and philosophical study method based on secondary data. Keywords: e-commmerce, legal protection.